Evaluation of vatiquinone drug-drug interaction potential in vitro and in a phase 1 clinical study with tolbutamide, a CYP2C9 substrate, and omeprazole, a CYP2C19 substrate, in healthy subjects. - Murase, Katsuyuki; Lee, Lucy; Ma, Jiyuan; Barrett, Rosemary; Thoolen, Martin (European Journal of Clinical Pharmacology, 2022)
Purpose : In this study, the drug-drug interaction potential of vatiquinone with cytochrome P450 (CYP) substrates was investigated in both in vitro and clinical studies. Methods: The inhibitory potential of vatiquinone on the activity of CYPs 1A2, 2B6, 2C8, 2C9, 2C19, 2D6, and 3A4/5 was assessed in vitro. In an open-label, drug-drug interaction study in 18 healthy human subjects, a single oral dose of 500 mg tolbutamide and 40 mg omeprazole was administered on day 1, followed by a washout of 7 days. Multiple oral doses of 400 mg vatiquinone (three times a day [TID]) were administered from day 8 to day 13 with coadministration of a single oral dose of 500 mg tolbutamide and 40 mg omeprazole on day 12. Results: In vitro, vatiquinone inhibited CYP2C9 (IC50 = 3.7 µM) and CYP2C19 (IC50 = 5.4 µM). In the clinical study, coadministration of vatiquinone did not affect the pharmacokinetic (PK) profile of tolbutamide and omeprazole. The 90% confidence intervals (CIs) of geometric least-square mean ratios for maximum plasma concentration (Cmax), areas under the plasma concentration–time curve (AUC0-t), and AUC0-inf of tolbutamide and omeprazole were entirely contained within the 80 to 125% no effect limit, except a minor excursion observed for Cmax of omeprazole (geometric mean ratio [GMR], 94.09; 90% CI, 78.70–112.50). Vatiquinone was generally well tolerated, and no clinically significant findings were reported. Conclusion: The in vitro and clinical studies demonstrated vatiquinone has a low potential to affect the pharmacokinetics of concomitantly administered medications that are metabolized by CYP enzymes.